Capital Accumulation and Unemployment: A Tale of Two Continents - Jim Malley; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2000)
In contrast to much recent work regarding the causes of European unemployment, in this paper, we emphasise the importance of capital accumulation. But unlike the few previous studies which have examined the relationship between capital accumulation and unemployment, we argue that what matters for the evolution of employment [and the unemployment rate] is not the absolute growth rate of a country quote s capital stock, but its evolution relative to other countries' capital stock. The empirical validity of the above statement is demonstrated for almost all OECD countries using quarterly time-series data from 1961-1995. More detailed evidence is also presented for Germany, Japan and the United Kingdom.
Keywords: 330; Unemployment; capital accumulation; international competition